Legal Protection Jurisdiction of Franchise Business (Franchise) in Indonesia - Nugroho, Maria Cecilia; Urbaniasi, Urbaniasi (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
In the increasingly developing era of globalization, economic growth continues to increase and is increasingly complex. The economy in Indonesia has experienced an increase, giving rise to many businesses or business practices, both small and medium businesses, and businesses that have large capital. These efforts certainly have a positive impact on society and the country, such as meeting the needs of an increasingly diverse society. One of the businesses that is currently developing is a franchise business. The purpose of our research is to find out the legal protection for franchisees and franchisors based on applicable regulations and to find out the legal aspects of franchise agreements. This study uses normative legal research methods whose implementation is focused on collecting secondary data (library material) which includes primary legal materials such as laws and regulations, primary legal materials such as books, articles, and so on. The franchise agreement is one aspect of legal protection given to related parties to avoid actions that are detrimental to these parties, including in providing legal protection for Intellectual Property Rights (IPR). A legally made franchise agreement applies as a law for those who make it as referred to in Article 1338 of the Civil Code. An agreement that has been made legally means that the agreement has fulfilled the conditions specified in the law.